Comparison of Law Enforcement of Narcotics Crimes in Indonesia and Thailand: Regulation and Case Handling - Putra, Telly Areska; Tumanggor, MS; Sriwidodo, Joko (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Narcotics are a global threat that requires comprehensive legal action, particularly in Indonesia and Thailand, as strategic areas for illicit trafficking. This study aims to analyze the comparative regulations, investigative methods, and effectiveness of law enforcement against narcotics crimes in both countries. The research method used is normative juridical with a legislative, conceptual, and analytical approach through secondary data from reports from 2024-2026. The results show that Indonesia maintains a strict policy with the threat of the death penalty but has begun to adopt restorative justice through Law No. 1 of 2023 and Prosecutor's Regulation No. 18 of 2021. In contrast, Thailand has undertaken a radical transformation through the Narcotics Code BE 2564 , which prioritizes public health and the decriminalization of certain substances. In practice, Indonesia excels in specialized investigative techniques, while Thailand is effective in border operations and asset seizures. In conclusion, both countries are transitioning from a punitive approach to a system that better balances legal and health aspects. The success of law enforcement in the future depends heavily on the integration of financial intelligence to impoverish drug lords and the effectiveness of rehabilitation in reducing recidivism rates, given the high number of suspects reaching tens of thousands each year in both regions